The Social Caring Character Development for Students through Youth Red Cross Extracurricular Activities - Rosnelly, Rosnelly; Montessori, Maria; Indrawadi, Junaidi; Suasti, Yurni (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The study aims to explain how to develop students' social caring character through PMR extracurricular activities. This research is qualitative research with a case study approach at SMKN 1 Lubuk Sikaping. Social care character development for students is carried out with various activities such as cleaning the school environment, picket guarding the field, providing assistance to victims of natural disasters, and distributing takjil during the month of Ramadan. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out by data reduction, data presentation, concluding, and verification. The findings of the study concluded that social care Sikaping education for students through PMR co-curricular activities. The results of the study concluded that the social care character development of students is aimed at all PMR members, which can be carried out through routine PMR activities, both through material and practice, such as providing assistance to disaster victims, cleaning the school environment, picketing the field, and distributing takjil during the month of Ramadan. This activity has an impact on the formation of the character of being responsive, independent, disciplined, skillful, and irresponsible.